SEIKATSU KAIZEN PADA MAHASISWA PROGRAM STUDI BAHASA JEPANG STBA YAPARI ANGKATAN 2018 DALAM PROGRAM INTERNSHIP DI JEPANG - Asep Achmad Muhlisian; Suci Dwi Lestari (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Jenderal Soedirman, 2026)
Abstract This study examines an overview of the forms of seikatsu kaizen and the impact of its application on STBA YAPARI Japanese Language Study Program students class of 2018 in an internship program in Japan. This study used qualitative research methods. The results of this research show that internship students experience forms of seikatsu kaizen in the aspects of health, work, finances, home, relationships and habits. The impact of implementing seikatsu kaizen felt by internship students includes the impact of getting to know yourself better, changing habits permanently, increasing personal development, reducing stress and increasing enthusiasm for change, bringing harmony to the surrounding environment, increasing personal well-being, and improving overall quality of life. whole. Key words: internship program, kaizen, seikatsu kaizen